THE AMS RADIOCARBON DATING OF POLLEN CONCENTRATE FROM THE LATE PLEISTOCENE ICE WEDGE OF THE BISON SECTION, KOLYMA REGION - Vasil'chuk Yu.K.; Vasil'chuk A.C.; Kim J.-Ch. (My University, 2003)
The new results of radio-carbon dating using accelerating mass spectrometry technique (AMS) for palynological concentrate extracted from syngenetic Late Pleistocene ice-wedge ices of Bison section are compared with palynological analysis data for the same samples and with results of radio-carbon AMS dating for two other organic fractions extracted previously from ice. Also the validity rate is established for different organic fractions' dating. The results enable adequate reconstruction and chronology of landscape' dynamics in the regional scale on the base of the dated spore and pollen extracts from vein ices.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен